2002
DOI: 10.1016/s0960-9822(02)01075-8
|View full text |Cite
|
Sign up to set email alerts
|

RIP4 Is an Ankyrin Repeat-Containing Kinase Essential for Keratinocyte Differentiation

Abstract: The epidermis is a stratified, continually renewing epithelium dependent on a balance among cell proliferation, differentiation, and death for homeostasis. In normal epidermis, a mitotically active basal layer gives rise to terminally differentiating keratinocytes that migrate outward and are ultimately sloughed from the skin surface as enucleated squames. Although many proteins are known to function in maintaining epidermal homeostasis, the molecular coordination of these events is poorly understood. RIP4 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
118
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 29 publications
12
118
0
Order By: Relevance
“…In contrast to WT skin, the outermost epidermal cell layers are nucleated in RIPK4 − / − skin (Figures 1a and c). This phenotype was originally described as parakeratosis, 3 defined as keratinization with retention of nuclei. However, patches of anuclear corneocytes are found beneath the outermost nucleated cells (Figures 1a and c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to WT skin, the outermost epidermal cell layers are nucleated in RIPK4 − / − skin (Figures 1a and c). This phenotype was originally described as parakeratosis, 3 defined as keratinization with retention of nuclei. However, patches of anuclear corneocytes are found beneath the outermost nucleated cells (Figures 1a and c).…”
Section: Resultsmentioning
confidence: 99%
“…The most striking characteristic of RIPK4 − / − mice is the epithelial fusion of all external orifices and the esophagus, as well as the partial attachment of limbs to the body wall 3 ( Figures 3a-f), but it remains unclear how these fusions arise. When we analyzed different embryonic stages, we found that the mouth cavity is initially formed in E12.5 RIPK4 − / − embryos, but the epithelia lining the oral cavity fuse completely at E13.5 ( Supplementary Figures S2F and G).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations